Annual Report on Exchange Arrangements and Exchange Restrictions 1979. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1979)
This paper highlights some particularly sharp movements in the effective exchange rates of a number of the currencies of major industrial countries during 1978 and early 1979. These changes followed sizable, but less pronounced movements in the effective exchange rates of some of these currencies in 1977. A number of major policy actions affecting exchange rates were announced by the United States during the period under review. In January 1978, the United States reaffirmed that it would intervene to the extent necessary to counter disorderly conditions in the exchange markets and that for this purpose it would utilize the Exchange Stabilization Fund of the US Treasury and the USD 20 billion swap network of the US Federal Reserve System. During the period under review, a number of other member countries adopted new exchange arrangements or modified their existing exchange arrangements. These changes reflected a continuation of the trend observed in recent years for members to adapt existing exchange arrangements to their own institutional circumstances and individual policy needs.